BMC Sports Science, Medicine and Rehabilitation - SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Sports Science, Medicine and Rehabilitation is an open access, peer reviewed journal that considers articles on all aspects of sports medicine and the exercise sciences, including rehabilitation, traumatology, cardiology, physiology, and nutrition.
Keywords: Orthopedics; Rehabilitation medicine; Sports medicine; Sports Medicine; Orthopedics; Rehabilitation Medicine